Upaya Hukum Pidana dalam Menangani Pedagang Rokok Tanpa Pita Cukai - Michael Stefanus Subnafeu; I Putu Edi Rusmana; I Made Wirya Darma; I Gusti Ayu Eviani Yuliantri (Cattleya Darmaya Fortuna, 2026)
This study analyzes criminal law enforcement in handling cigarette traders without excise stamps, a crucial issue in protecting state revenue and promoting economic justice. Selling cigarettes without excise stamps violates Law Number 39 of 2007 on Excise, which prescribes imprisonment and/or fines for offenders. Such practices harm the state fiscally, distort fair competition, and lower public compliance with the law. The research applies a normative legal method focusing on positive legal norms (law in the book), using statute, conceptual, and case approaches. Data were collected through library research and analyzed qualitatively by interpreting relevant laws, legal theories, and case studies. Findings show that criminal sanctions, as stipulated in Article 54 of Law Number 39 of 2007, are essential in curbing the illegal cigarette trade. Law enforcement agencies namely the Directorate General of Customs and Excise, the Police, and the Prosecutor’s Office play a vital role in supervision, investigation, and prosecution. However, effectiveness remains limited due to resource constraints, weak inter-agency coordination, low legal awareness, and economic motives among small traders. Improving enforcement requires stronger institutional cooperation, digital surveillance, continuous legal education, and economic empowerment for traders to transition to legal products. Consistent and fair enforcement is expected to enhance deterrence, increase compliance, and support state fiscal protection.